Monoclonal Antibody Therapy and Renal Transplantation: Focus on Adverse Effects - Zaza, Gianluigi (MDPI, 2014)
A series of monoclonal antibodies (mAbs) are commonly utilized in renal transplantation as induction therapy (a period of intense immunosuppression immediately before and following the implant of the allograft), to treat steroid-resistant acute rejections, to decrease the incidence and mitigate effects of delayed graft function, and to allow immunosuppressive minimization. Additionally, in the last few years, their use has been proposed for the treatment of chronic antibody-mediated rejection, a major cause of late renal allograft loss. Although the exact mechanism of immunosuppression and allograft tolerance with any of the currently used induction agents is not completely defined, the majority of these medications are targeted against specific CD proteins on the T or B cells surface (e.g., CD3, CD25, CD52). Moreover, some of them have different mechanisms of action. In particular, eculizumab, interrupting the complement pathway, is a new promising treatment tool for acute graft complications and for post-transplant hemolytic uremic syndrome. While it is clear their utility in renal transplantation, it is also unquestionable that by using these highly potent immunosuppressive agents, the body loses much of its innate ability to mount an adequate immune response, thereby increasing the risk of severe adverse effects (e.g., infections, malignancies, haematological complications). Therefore, it is extremely important for clinicians involved in renal transplantation to know the potential side effects of monoclonal antibodies in order to plan a correct therapeutic strategy minimizing/avoiding the onset and development of severe clinical complications.